Inferior frontal oscillations reveal visuo-motor matching for actions and speech: evidence from human intracranial recordings. (December 2015) - Halje, Pär; Seeck, Margitta; Blanke, Olaf; Ionta, Silvio
Abstract: The neural correspondence between the systems responsible for the execution and recognition of actions has been suggested both in humans and non-human primates. Apart from being a key region of this visuo-motor observation-execution matching (OEM) system, the human inferior frontal gyrus (IFG) is also important for speech production. The functional overlap of visuo-motor OEM and speech, together with the phylogenetic history of the IFG as a motor area, has led to the idea that speech function has evolved from pre-existing motor systems and to the hypothesis that an OEM system may exist also for speech. However, visuo-motor OEM and speech OEM have never been compared directly. We used electrocorticography to analyze oscillations recorded from intracranial electrodes in human fronto-parieto-temporal cortex during visuo-motor (executing or visually observing an action) and speech OEM tasks (verbally describing an action using the first or third person pronoun). The results show that neural activity related to visuo-motor OEM is widespread in the frontal, parietal, and temporal regions. Speech OEM also elicited widespread responses partly overlapping with visuo-motor OEM sites (bilaterally), including frontal, parietal, and temporal regions. Interestingly a more focal region, the inferior frontal gyrus (bilaterally), showed both visuo-motor OEM and speech OEM properties independent of orolingual speech-unrelated movements. Building on the methodological advantages in human invasive electrocorticography, the present findings provide highly precise spatial and temporal information to support the existence of a modality-independent action representation system in the human brain that is shared between systems for performing, interpreting and describing actions. Highlights: Human electrocorticography of action-speech correspondence in inferior frontal gyrus. Extensive neural networks show selective mirror-like properties for action and speech. Multimodal representations of action and speech in fronto-temporo-parietal regions.